The effects of different irrigation levels on grain yield and yield components of four chickpea cultivars (Cicer arietinum L.) in Mashhad climatic condition - Salman Anjamshoaa; Hamid Moeinrad; Hosein Ebrahimi (پژوهش‌های حبوبات ایران)
In order to study the effects of different irrigation levels on yield, yield components and drought tolerance of four chickpea cultivars, a farm experiment was conducted in Mashhad climatic condition during 2008-2009 growing season. Four irrigation levels including: T1= 100% ETC (Full irrigation), T2= 90% ETC (deficit irrigation), T3=80% ETC (deficit irrigation) and T4=50% ETC (deficit irrigation) and four chickpea cultivars (Jam, Karaj 12-60-31, Kaka and ILC482) were compared in a split plot layout based on randomized complete block design with three replications. The irrigation levels were imposed as main plot and chickpea cultivars as subplot. In each level of irrigation, based on national water document (using NETWAT software) and by the method of Penman Monteith, water requirement was determined. The results showed that different levels of irrigation had significant effects on grain yield, biological yield, harvest index, number of pods per m2, number of seeds per m2 and weight of 100 chickpea seeds. By increasing the rate of supplied water, number of pods and seeds per m2, the weight of 100 chickpea seeds and consequently, grain yield increased, significantly. In all irrigation levels, Kaka and Karaj 12-60-31 cultivars had the highest (930 Kg/ha) and the lowest (166 Kg/ha) seed yield, respectively. In this study, the most drought tolerant cultivars to drought were Kaka, ILC482 and Jam, respectively. In full irrigation treatment, the yield of ILC482 cultivar was lower than Jam cultivar, but in deficit irrigation treatments (T3 and T4) the yield of Jam cultivar was higher than ILC482 cultivar, considerably and in comparison to the other cultivars, its measured qualities less affected by deficit irrigation. Results of this experiment showed that ILC482 cultivar may be recommended as a high tolerant cultivar to drought stress.